Women in Pastoral Societies and the Church in Kilosa, Tanzania - Massoi, Lucy Willy (African Study Monographs, 2026)
Given the strong patriarchal systems still evident among the pastoral Maasai society one might think that the life of the Maasai women is bleak and difficult; but this is no longer the case. First-hand observation, in-depth interviews and group discussions obtained through an ethnographic-inspired approach revealed that increasingly in Kilosa Tanzania, there is new hope for the women once regarded as servants and properties of men under the male-dominated empire. Where state structures, services and civil society are thin on the ground, the church is increasingly becoming involved in this transformation process. Women are increasingly learning to negotiate and manipulate rules and norms, to straddle different institutions, both formal and informal and to resist the oppressive culture. The church is facilitating and promoting self-awareness to women of their own value and potentials, even as widows, single women or divorcees. Local communities and women in particular are increasingly supported, educated and empowered to manage their own lives and shoulder their reproductive and productive roles as well as decision-making roles once regarded a male-only dominion. Some have even ventured into politics and are demanding their rights to land within the patriarchal-dominated system. While the church has tried to penetrate and fight the patriarchal system, much remains to be done to fight the deep-rooted system in Maasai society.